2008
DOI: 10.1007/s11250-008-9171-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estrus synchronization treatments on somatic cell count of transitional-anestrus Awassi ewes’ milk

Abstract: An experiment was conducted to examine the effect of estrus synchronization protocols and steroid hormones concentrations on somatic cell count (SCC) of transitional-anestrus local-Damascus cross goats' milk. Fifty-six goats (2-4-year old) were randomly assigned to three groups: fluorogestone acetate (FGA, n = 19), FGA-Prostaglandin (FGA-PGF, n = 19) and control (n = 18) groups. Intravaginal sponge containing 40 mg FGA was inserted for 13 days and an injection of 600 IU equine chorionic gonadotropin (eCG) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…These results agreed with those in dairy cattle (Cowan andLarson, 1979, Anderson et al, 1983), yet, disagreed with those found in dairy goat and dairy ewe in which oestrus appeared to provoke a significant increase in SCC (Aleandri et al, 1994;Mc dougall et Voermans, 2002;Christodoulopoulos et al, 2008;Talafha et al, 2009). Table 2.…”
Section: Milk Composition and Sccsupporting
confidence: 50%
“…These results agreed with those in dairy cattle (Cowan andLarson, 1979, Anderson et al, 1983), yet, disagreed with those found in dairy goat and dairy ewe in which oestrus appeared to provoke a significant increase in SCC (Aleandri et al, 1994;Mc dougall et Voermans, 2002;Christodoulopoulos et al, 2008;Talafha et al, 2009). Table 2.…”
Section: Milk Composition and Sccsupporting
confidence: 50%
“…The determination of the somatic cell count per milliliter of collected milk was performed according to Newman-Lampert's stain procedure (Kolmer et al 1959;Pusch et al 1984;Kassaify et al 2007;Talafha et al 2009). Briefly, a smear of 10 μl of each milk sample was fixed on a microscopic slide.…”
Section: Sampling and Immunological Determinationsmentioning
confidence: 99%
“…Bovine viral diarrhea (BVD) is a common disease reported in cattle populations worldwide and bovine viral diarrhea virus (BVDV) is frequently identified as a causative pathogen for BRD outbreaks. The BVDV is one of more than 20 pathogens that comprise the broader disease spectrum of the BRD complex (Richer et al, 1988; Wittum et al, 2001; Becher et al, 2003; Poletto et al, 2004; Talafha et al, 2009; Choi and Song, 2010; Schneider et al, 2010). Of cattle tested for BVD-PI in numerous studies worldwide, the presence of BVDV antibodies were identified in 60–85% of cattle and an additional 1–2% were persistently infected (Houe, 1999).…”
Section: Introductionmentioning
confidence: 99%